sIgA, peroxidase and collagenase in saliva of smokers aggressive periodontal patients - Myriam A. Koss; Cecilia E. Castro; Agustina M. Gramajo; María E. López (Elsevier, 2016)
Background: Tobacco smoking is strongly associated with destructive periodontal disease, alveolar bone loss and poor response to periodontal therapy. The aim of this study was to investigate the effect of smoking on antimicrobials and destructive proteins in the saliva of patients with generalized aggressive periodontal disease. Material and methods: The study group consisted of 55 adult subjects. They were classified according to their clinical diagnoses either as having generalized aggressive periodontitis (n = 27; 13 smokers and 14 non-smokers) or as periodontitis-free control group (n = 28; 14 smokers and 14 non-smokers). Total proteins, sIgA, peroxidase and collagenase were quantified in whole saliva. Data were analyzed using one-way ANOVA and Tukey tests. Results: Statistical differences were found between smokers with periodontal disease and healthy control subjects for sIgA, and between non-smokers with periodontal disease and healthy control subjects for peroxidase. Collagenase activity was higher in smokers and non-smokers with periodontal disease, and tobacco use was found to increase collagenase activity in healthy subjects. Conclusion: Whole saliva from all patients with periodontal disease had higher sIgA and lower peroxidase content. Smokers with periodontitis had higher sIgA than smokers without periodontitis. Smokers with and without periodontitis had higher collagenase activity than non-smokers (with and without periodontitis).